1998
DOI: 10.1097/00005768-199809000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Physical fitness, physical activity, and functional limitation in adults aged 40 and older

Abstract: These data support a protective effect of physical fitness and physical activity on functional limitation among older adults and extend this protective effect to middle-aged men and women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
0
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(60 citation statements)
references
References 23 publications
5
53
0
2
Order By: Relevance
“…Using different definitions, the prevalence of functional limitations was reported to be between 8 and 20% in the USA [17, 18], around 17% in France [19], 15% or more (depending on method) in the UK [20] and between 11 and 19% in Sweden [10]. Although direct comparisons are difficult, our data suggest relatively high levels of functional limitations in these Central and Eastern European population samples, particularly among women.…”
Section: Discussionmentioning
confidence: 73%
“…Using different definitions, the prevalence of functional limitations was reported to be between 8 and 20% in the USA [17, 18], around 17% in France [19], 15% or more (depending on method) in the UK [20] and between 11 and 19% in Sweden [10]. Although direct comparisons are difficult, our data suggest relatively high levels of functional limitations in these Central and Eastern European population samples, particularly among women.…”
Section: Discussionmentioning
confidence: 73%
“…3133 A cohort study of middle-age men and women followed over 5 years demonstrated that physical limitations were higher among women than men and that physically active individuals reported fewer functional limitations than their less active counterparts. 34 Moderate physical exercise with a directed program designed to enhance cardiovascular fitness, muscular endurance, and flexibility was associated with improved functional abilities in patients with fibromyalgia. 35 …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, for mental health, vigorous physical activity may not provide any additional benefits to lower intensity activity [14, 32]. In addition, good cardiorespiratory fitness is a key component of good functioning [33] and has been associated with a lower risk of sickness absence [34, 35], as well as disability retirement [36]. For mortality, fitness has shown stronger associations compared to physical activity, but they may both have independent beneficial effects on health [37].…”
Section: Discussionmentioning
confidence: 99%